Financing and borrowing activities 2023 (European Investment Bank, 2025)
This report lays out the European Investment Bank’s public policy goals and details its investments in the projects that support them. It provides a breakdown of all projects signed in 2023 within the European Union and beyond. The report tracks our investment in different sectors in each EU country over the last five years. It also includes a summary of the European Investment Fund’s 2023 results. These numbers show that — even in a year marked by geopolitical tensions, supply chain disruption and the ongoing effects of the COVID-19 pandemic — the European Investment Bank Group remained steadfast in its commitment to innovation, sustainability and equality.